A planning practice method to assess the potential for cycling and to design a bicycle network in a starter cycling city in Portugal - Fonseca, Fernando Pereira da (2023)
There is growing recognition of the potential for cycling to provide more sustainable and active urban mobility. In Portugal, the National Strategy for Active Mobility aims at increasing the bicycle modal share from the current level of below 1% to 10% by 2030. This paper describes a planning practice method to assess the potential for cycling and to design a bicycle network in Ponte de Lima, a small starter Portuguese city, which only has some disconnected cycle lanes. The method consists of assessing the target population and target area attributes through a Geographic Information System (GIS) and Space Syntax operations. Results showed that the potential for cycling in Ponte de Lima is hindered by the hilly terrain, by the low population density and by the low percentage of the young population. The compact urban structure and the level of street integration enhances topological proximity and makes using a bicycle convenient. The proposed bicycle network comprises segregated cycle lanes, colored cycle lanes and a set of streets where cycling coexists with other road users. Adopting complementary measures, such as traffic calming and bicycle-sharing services, could be decisive to make cycling more appealing in Ponte de Lima and to help the city in reaching the ambitious goal of the National Strategy for Active Mobility.